Notice of Forfeiture to Incarcerated Individuals: Did the Supreme Court Get it Right in Dusenbery v. United States? - Michelle Murphy-Riveria (Washington University Journal of Law & Policy, 2002)
This Recent Development addresses whether or not the Due Process Clause of the Fifth Amendment requires that the federal government provide actual notice of forfeiture to incarcerated individuals, and it proposes that the Supreme Court erred in its recent decision in Dusenbery.
Keywords: Notice (Law); Prisoners; Dusenbery v. United States 534 U.S. 161 (2002); Forfeiture; United States; Prisons